Epigallocatechin-3-gallate inhibits doxorubicin-induced inflammation on human ovarian tissue. Issue 5 (14th May 2019) - Fabbri, R; Macciocca, M; Vicenti, R; Caprara, G; Piccinni, MP; Paradisi, R; Terzano, P; Papi, A; Seracchioli, R
Abstract : Chemotherapy protocol can destroy the reproductive potential of young cancer patients. Doxorubicin (DOX) is a potent anthracycline commonly used in the treatment of numerous malignancies. The purpose of the study was to evaluate the ovarian toxicity of DOX via inflammation and the possible protective effect of the green tea polyphenol epigallocatechin-3-gallate (EGCG). Ovarian tissue of three patients was cultured with 1 µg/ml DOX and/or 10 µg/ml EGCG for 24 and 48 h. Levels of inflammatory factors were determined by quantitative Real-Time PCR, western blot, zimography, and multiplex bead-based immunoassay. Morphological evaluation, damaged follicle count and TUNEL assay were also performed. DOX influenced inflammatory responses by inducing a significant increase in the expression of pro-inflammatory cytokines, such as tumor necrosis factor-α (TNF-α) and cyclooxigenase-2 (COX-2), of inflammatory interleukins (IL), such as interleukin-6 (IL-6) and interleukin-8 (IL-8), and the inflammatory proteins mediators metalloproteinase-2 and metalloproteinase-9 (MMP2 and MMP9). IL-8 secretion in the culture supernatants and MMP9 activity also significantly raised after DOX treatment. Moreover, a histological evaluation of the ovarian tissue showed morphological damage to follicles and stroma after DOX exposure. EGCG significantly reduced DOX-induced inflammatory responses and improved the preservation of follicles. DOX-induced inflammation could be responsible for the ovarian function impairment of chemotherapy. EGCG could have a protective role in reducing DOX-mediated inflammatory responses in human ovarian tissue.